Effects of variety and chemical regulators on cold tolerance during maize germination - WANG, Li-jun; ZHANG, Ping; WANG, Ruo-nan; WANG, Pu; HUANG, Shou-bing (Journal of Integrative Agriculture, 2018)
Maize growth and development is affected by low temperature (LT) especially at the early stages of development. To describe the response of different varieties to LT stress and determine an effective method to cope with LT stress, maize hybrids Zhengdan 958 (ZD 958) and Danyu 39 (DY 39) were planted and grown at 10 and 25°C, respectively. Effects of the chemicals potassium chloride (KCl), gibberellin (GA3), 2-diethylaminoethyl-3,4-dichlorophenylether (DCPTA), and all three combined chemicals (KGD) on coping with LT stress were tested by seed priming. The varieties performed significantly different at 10°C. Compared to leaf, root growth was more severely affected by LT stress. Root/leaf ratio is likely a more reliable parameter to evaluate cold tolerance based on its close correlation with leaf malondialdehyde (MDA) content (R=−0.8). GA3 advanced seed germination by about 2 days compared with control treatment of water. GA3 and DCPTA both resulted in lower leaf MDA content and higher leaf and root area, and root/leaf ratio. KCl resulted in the highest evenness of plant height. KGD performed the best in increasing cold tolerance of maize morphologically and physiologically. Strategies to increase maize tolerance of cold stress, such as variety breeding or chemical selection, would increase maize yield especially at high-latitude regions and have great implications for food security.